The Synthesis of Organic Oils Blended Magnetorheological Fluids with the Field-Dependent Material Characterization - Rakesh Jinaga (International Journal of Molecular Sciences, 2019)
Automation is one of the trending terminologies in the field of engineering to achieve various sensors and actuators such as the hydraulic system. Smart fluid is also one of the hot topics for researchers to develop a type of actuator in many control systems since the fluid’s rheological characteristics can be controlled or tuned by the intensity of the external stimuli. In this work, a new smart fluid of magnetorheological (MR) fluid is proposed and its field-dependent rheological characteristics are experimentally identified. An MR fluid using the carrier fluid as the blend of three different fluids, namely silicon oil, honey, and organic oil is prepared. In addition, two types of natural oils are used, sunflower oil and cottonseed oil. The samples are prepared using the blend as the carrier fluid, electrolytic iron powder coated with guar gum as the dispersed phase, and oleic acid as an additive. The quantity of oleic acid is optimized for 30% by weight of electrolytic iron powder. Two samples based on sunflower and cottonseed oil are synthesized and characterized for shear viscosity and shear stress with respect to shear rate subjected to a variable magnetic field. The blend-based MR fluid shows about 10% improvement over the sedimentation rate of silicon oil-based MR fluid as compared to that to conventional MR fluid. The cottonseed oil blend-based MR fluid performs better than sunflower-based fluid in terms of the viscosity and structure.